Rogi Parīkṣā In Ayurveda: A Critical Review Of Dvividha, Trividha, Pratyakṣa, Anumāna And Āptopadeśa Examination Methods (The Review of Diabetic Studies, 2025)
Rogi Parīkṣā (examination of the patient) forms the cornerstone of Ayurvedic diagnosis and clinical practice. Classical Ayurvedic texts emphasize systematic examination through perceptual, inferential, and authoritative methods for accurate diagnosis and successful treatment. The present article critically reviews the concepts of Dvividha Parīkṣā (twofold examination), Trividha Parīkṣā (threefold examination), Pratyakṣa Parīkṣā (direct observation), Anumāna Parīkṣā (inferential examination), and Āptopadeśa (authoritative instruction) based on classical references from Caraka Saṁhitā. The article discusses the philosophical and practical aspects of these diagnostic approaches and highlights their relevance in clinical evaluation. The study demonstrates that Ayurvedic diagnostic methods involve comprehensive assessment through sensory perception, inference, interrogation, and scriptural wisdom, thereby ensuring holistic understanding of disease and patient status.